Building the evidence base for urgent action: HIV epidemiology and innovative programming for men who have sex with men in sub‐Saharan Africa. Issue 4 (2nd December 2013) - Wolf, R Cameron; Cheng, Alison Surdo; Kapesa, Laurent; Castor, Delivette
Abstract : While still an understudied area, there is a growing body of studies highlighting epidemiologic data on men who have sex with men (MSM) in sub‐Saharan Africa (SSA) which challenge the attitudes of complacency and irrelevancy among donors and country governments that are uncomfortable in addressing key populations (KPs). While some of the past inaction may be explained by ignorance, new data document highly elevated and sustained HIV prevalence that is seemingly isolated from recent overall declines in prevalence. The articles in this series highlight new studies which focus on the stark epidemiologic burden in countries from concentrated, mixed and generalized epidemic settings. The issue includes research from West, Central, East and Southern Africa and explores the pervasive impact of stigma and discrimination as critical barriers to confronting the HIV epidemic among MSM and the intersecting stigma and marginalization found between living with HIV and sexual minority status. Interventions to remove barriers to service access, including those aimed at training providers and mobilizing communities even within stigmatized peri‐urban settings, are featured in this issue, which further demonstrates the immediate need for comprehensive action to address HIV among MSM in all countries in the region, regardless of epidemic classification.